Occurrence of AM fungi in Xanthium strumarium L.plants of Osmanabad District - Sarwade, Prakash P; Gaisamudre, Kavita N; Bhale, U N (Journal of Experimental Sciences, 2012)
A survey of the arbuscularmycorrhizal (AM) status associated with Xanthium strumariumL plants growing and distributed in Osmanabad district of Marathwada region in Maharashtra state. The result showed that all the different sites Xanthium strumarium L. plants had AM fungal association in the roots and spore population in the rhizosphere soil. However, maximum percent root colonization of AM fungi was observed in Paranda sites (98 %) followed by others, while minimum in Omerga sites (58 %).Paranda sites (300) showed more spore density whereas less in Kallam sites (59). Total five genera of AMF was identified up to species level in which Acaulosporaspp and Glomusspp were found dominate followed by, Sclerocystisspp, Entrophosphoraspp and Gigasporaspp were found poorely distributed.